The Politics of Health Policy in Bombana District: A Qualitative Analysis of Interactions among Government, Legislature, and Stakeholders - Ramadhan Tosepu; Devi Savitri Effendy; Intan Anugrah Pratiwi (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Health policymaking is inherently political, shaped by interactions among government institutions, legislatures, and diverse stakeholders. In decentralized settings such as Indonesia, these interactions influence agenda setting, resource allocation, implementation, and policy change. However, limited evidence exists on the political dynamics underpinning local health policymaking at the district level. Objectives: This study aimed to explore the politics of health policymaking in Bombana District through an analysis of interactions among government actors, legislative institutions, and key stakeholders. Methods: A qualitative study design was employed using in-depth interviews with six purposively selected key informants representing government, legislative, professional organizations, health service providers, and civil society. Data were analyzed using thematic analysis informed by policy network and advocacy coalition perspectives. Results: Six major themes emerged: policy actor networks, advocacy coalitions and competing interests, health policy formulation processes, power relations and political negotiation, policy implementation dynamics, and policy change and learning. Findings revealed that executive actors held dominant influence in agenda setting and resource allocation, while policymaking was also shaped by negotiation, coalition-building, and inter-actor collaboration. Implementation was constrained by resource limitations and political dynamics, whereas policy learning supported adaptation and change. Conclusion: Health policymaking in Bombana operates as a networked and politically mediated governance process rather than a purely technical exercise. Strengthening collaborative governance, participatory decision-making, and evidence-informed policy processes may improve health policy responsiveness and implementation in decentralized settings. Keywords: health policy politics; policy networks; advocacy coalitions; decentralized governance; qualitative study